2017
DOI: 10.1128/jvi.00225-17
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Vpx-Mediated SAMHD1 and Vpr-Mediated Host Helicase Transcription Factor Degradation by Selective Disruption of Viral CRL4 (DCAF1) E3 Ubiquitin Ligase Assembly

Abstract: The lentiviral accessory proteins Vpx and Vpr are known to utilize CRL4 (DCAF1) E3 ligase to induce the degradation of the host restriction factor SAMHD1 or host helicase transcription factor (HLTF), respectively. Selective disruption of viral CRL4 (DCAF1) E3 ligase could be a promising antiviral strategy. Recently, we have determined that posttranslational modification (neddylation) of Cullin-4 is required for the activation of Vpx-CRL4 (DCAF1) E3 ligase. However, the mechanism of Vpx/Vpr-CRL4 (DCAF1) E3 liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 86 publications
1
23
0
Order By: Relevance
“…Thus, our data support that zinc is not important for the FIV Vif-CUL5 interaction, as discussed previously (18). Other studies have demonstrated that TPEN treatment blocks the function of HIV-1 Vif and Vpr and SIVmac Vpx (39). These findings indicate that in the group of lentiviruses, there are zinc-dependent (e.g., HIV-1 and BIV) and zinc-independent (e.g., FIV and MVV) Vif proteins.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, our data support that zinc is not important for the FIV Vif-CUL5 interaction, as discussed previously (18). Other studies have demonstrated that TPEN treatment blocks the function of HIV-1 Vif and Vpr and SIVmac Vpx (39). These findings indicate that in the group of lentiviruses, there are zinc-dependent (e.g., HIV-1 and BIV) and zinc-independent (e.g., FIV and MVV) Vif proteins.…”
Section: Discussionsupporting
confidence: 91%
“…Three HIV/SIV accessory proteins (Vpr, Vpx, and Vif) bind zinc, which is essential for the assembly of their E3 ligase complexes (39)(40)(41). Zinc is also required for BIV Vif-CUL2 binding, while the MVV Vif-CUL5 interaction does not need zinc (42).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is little evidence indicating whether such Vpr sequences mimic the full role played by typical HHCC zinc-binding motifs. Recently, some studies have revealed that the HHCH motif of HIV-1 Vpr, which is positioned parallel to that of HIV-2 Vpx, may show capacity to interact with the E3 ligase complex [28]. However, whether the potential zinc-binding motif contributes to the function of Vprs remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that a zinc-binding motif is essential for maintaining both Vpr and Vpx. The potential zinc-binding motif of Vpr/Vpx also engaged E3 ubiquitin ligase complex formation and hijacked it to induce cellular factor degradation [28]. By contrast, flexible C-terminal domains exhibited sequence diversity compared to the central region of Vpr/Vpx proteins.…”
Section: Phylogeny Multiple Alignments and Expression Of Vpr/x Frommentioning
confidence: 99%
“…Moreover, other proteins involved in DNA repair (i.e. uracil-DNA glycosylase 2, single-strand selective monofunctional uracil-DNA glycosylase and more recently the DNA helicase/translocase HLTF) are degraded by Vpr through an E3 ubiquitin ligase complex composed of VPRBP (Vpr binding protein or DCAF), DDB1 and cullin 4A (CUL4A) [ 38 40 , 44 , 54 ]. Using the neddylation and CUL4A inhibitor MLN4924 we still observed efficient PHF13 degradation by Vpr.…”
Section: Discussionmentioning
confidence: 99%